Education For Sustainable Development in Preservice Teacher Program: A Bibliometric Method - Elvia Ivada (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Sustainability education or education for sustainable development is crucial for advancing eco-conscious growth. In this context, the teacher is essential in delivering knowledge and fostering awareness of sustainability among students. As the younger generation, students will contribute to the development of businesses and the country. Consequently, the behavior of the generation should correlate with sustainability principles. Teachers also influence the formation of a young generation equipped with a deep understanding and awareness of sustainability, shaping future behaviors. Based on this discovery, sustainability education for a prospective teacher is essential. Therefore, this study aims to provide a comprehensive analysis of trends related to sustainability education for a preservice teacher. Method: The study adopted a bibliometric method using the VOS viewer and analysis tools available on Scopus. The analyzed articles focused on sustainability education for a preservice teacher, published in the Scopus database between 1998 and 2024. Results: The results showed that several areas within this field required further publication, offering opportunities for scholars to explore. Novelty: The study was the first to explore sustainability education within the context of preservice teacher training.